Komparasi Model Pendidikan Islam antara Muhammadiyah dan Persatuan Islam - Zilal Afwa Ajidin; Asep Ajidin (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2022)
Islamic education programs have developed since before Indonesia's independence. However, de facto still experiences ups and downs in its implementation. In this study, the authors compare two Islamic community organizations, namely Muhammadiyah and Persatuan Islam, by taking case studies, namely Mu'allimin Muhammadiyah Yogyakarta and Mu'allimin Persatuan Islam Tarogong Garut. The sample was taken because both of them are the largest mu'allimin from each of the Islamic community organizations. This study aims to find out how the Islamic education model implemented by the school in facing the challenges of the times. The results showed that the two mu'allimin had quite different models in carrying out their curriculum. However, they have similarities in terms of vision and mission, namely creating Islamic religious teachers who are able to adapt to their environment. The conclusion obtained from this study is that each mu'allimin is able to become a superior school in their respective environments with the system they implement. The model of Islamic religious education for the two mu'allimin is the organism model. Keywords: Islamic Educational Model, Muhammadiyah, Persatuan Islam